Pemberdayaan Ibu-Ibu PKK Dalam Menumbuhkan Jiwa Kewirausahaan Melalui Pelatihan Pembuatan Chicken Nugget Di Desa Ridogalih Kabupaten Bekasi - Ahmad Gunawan (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2019)
Independent women are one indicator of increasing prosperous in the family economy. Being an educated society and earning become the dream of everyone, especially women. Women can have a huge contribution in overcoming shortages, poverty and unemployment, because it needs education, training and empowerment of women, especially PKK members in Ridogalih Village, Bekasi Regency, who have entrepreneurial spirit. The improvement and development of entrepreneurial attitudes in this service, through training, skills and empowerment of PKK member, is very important, the aim is to provide understanding to women; even though they are at home, they don't work out of the house but still have the potential to earn. and motivate them to open a business by releasing all the knowledge, abilities and skills so they have to achieve income. Efforts to foster and develop the potential of the PKK member of village of Ridogalih, including through training in skills in making chicken nuggets. Nugget is a product that is liked by many people and is expected to provide family income, especially for PKK members. After going through this skills training, they are motivated to become an entrepreneur. Keywords: Entrepreneurship, Empowerment, Training, PKK members.